Psychometric Evaluation of the Kansas City Cardiomyopathy Questionnaire in Men and Women With Heart Failure. (September 2021) - Hejjaji, Vittal; Tang, Yuanyuan; Coles, Theresa; Jones, Philip G.; Reeve, Bryce B.; Mentz, Robert J.; Spatz, Erica S.; Dunlay, Shannon M.; Caldwell, Brittany; Saha, Anindita; Tarver, Michelle E.; Tran, Andy; et al.
Abstract : Background: The Kansas City Cardiomyopathy Questionnaire (KCCQ) has been psychometrically evaluated in multiple heart failure (HF) populations, but the comparability of its psychometric properties between men and women is unknown. Methods: Data from 3 clinical trials (1 in stable HF with preserved ejection fraction, 1 each in stable and acute HF with reduced ejection fraction) and 1 prospective cohort study (stable HF with reduced ejection fraction), incorporating 6773 men and 3612 women with HF, were used to compare the construct validity, internal and test-retest reliability, ability to detect change, predict mortality and hospitalizations and minimally important differences between the 2 sexes. Interactions of the KCCQ overall summary and subdomain scores by sex were independently examined. Results: The KCCQ-Overall Summary score correlated well with New York Heart Association functional class in both sexes across patients with stable (correlation coefficient: −0.40 in men versus −0.49 in women) and acute (−0.37 in men versus −0.34 in women) HF. All KCCQ subdomains demonstrated concordant relationships with relevant comparison standards with no significant interactions by sex in 19 of 21 of these construct validity analyses. All KCCQ scores were equally predictive and other psychometric evaluations showed similar results by sex: test-retest reliability (intraclass correlation coefficient 0.94 in men versus 0.92 in women), responsive to change (standardized response mean 1.01 in both sexes), as were the minimally important differences and internal reliability. Conclusions: The psychometric properties of the KCCQ, in terms of validity, prognosis, reliability, and sensitivity to change, are comparable in men and women with HF with preserved ejection fraction and HF with reduced ejection fraction. Abstract : Supplemental Digital Content is available in the text.